2002
DOI: 10.1520/jfs2001150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 1,2-Indanedione, a Latent Fingerprint Reagent on Subsequent DNA Profiling

Abstract: The compound 1,2-indanedione was recently introduced in our laboratory as an operational reagent for developing latent fingerprints on porous surfaces. As part of the reagent implementation, a study was carried out in order to determine whether either of the two operational 1,2-indanediones formulations interferes with further DNA profiling. Both formulations are based on HFE7100 solvent. One is acidic and the other neutral. In a controlled experiment, known donors attached stamps to envelopes by licking them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Latent fingerprints on copy paper treated with single‐reagent and sequential fingerprint development processes produced DNA profiles with varying degrees of success. The single‐reagent treatments that were the least harmful to downstream DNA analysis were IND‐Zn and IND‐Zn/laser, a conclusion that has been demonstrated previously [33]. For the sequential treatments containing IND‐Zn and IND‐Zn/laser, the DNA yield and overall quality of the STR profiles generally decreased with the addition of each sequential treatment (e.g., ninhydrin, ORO, PD).…”
Section: Discussionsupporting
confidence: 64%
“…Latent fingerprints on copy paper treated with single‐reagent and sequential fingerprint development processes produced DNA profiles with varying degrees of success. The single‐reagent treatments that were the least harmful to downstream DNA analysis were IND‐Zn and IND‐Zn/laser, a conclusion that has been demonstrated previously [33]. For the sequential treatments containing IND‐Zn and IND‐Zn/laser, the DNA yield and overall quality of the STR profiles generally decreased with the addition of each sequential treatment (e.g., ninhydrin, ORO, PD).…”
Section: Discussionsupporting
confidence: 64%
“…Azoury et al, [76] reported that IND did not affect the isolation and amplification of STRs examined and therefore, DNA could be successfully typed from such processed items. No variations were observed in the STR profiles generated from processed and unprocessed envelopes and stamps.…”
Section: Effect Of 12-indanedione Processing On Dna Analysismentioning
confidence: 99%
“…A sensitive method for the quantitation of genomic DNA by Alu amplification is presented (27). The effect of 1,2-indanedione, a latent fingerprint detection reagent, on subsequent DNA profiling is described (28). The theory and application of the transfer of trace quantities of DNA through skin contact is reviewed (29).…”
Section: Forensic Dna Analysismentioning
confidence: 99%
“…Excellent performance of 1,2-indanedione as a latent fingerprint detection reagent has been reported (216). The effect of 1,2-indanedione, a latent fingerprint reagent, on subsequent DNA profiling has been studied (217). Chemical processes involved in the development of latent fingerprints using the cyanoacrylate fuming method have been studied (218).…”
Section: Trace Evidencementioning
confidence: 99%